Metabolic pathways of agrochemicals - Roberts, T. R. 1943-; Hutson, D. H.
This important publication provides a comprehensive summary of data and information on the metabolism and chemical degradation of agrochemicals in soils, plants and animals. Part 1, Herbicides and Plant Growth Regulators, and Part 2, Insecticides and Fungicides, together provide a major bibliography, as each entry is fully referenced. Contents include metabolic products, pathways and mechanisms, together with useful details on physico-chemical properties and mode of action. Both parts are organised by class of chemical for easy reference. There are separate entries for each pesticide, covering most commercially available chemicals in use today. In addition, an overview of the metabolism of each major class provides the reader with an informed summary of key similarities and significant differences between individual chemicals. Information is based primarily on literature from the past 40 years of research, together with some important, previously unpublished work provided by the agrochemical companies. Presented in a systematic, easy-to-read style, with extensive indexing to facilitate the rapid location of required information and the comparison of related compounds, Metabolic Pathways of Agrochemicals is an invaluable reference for chemists, biochemists and biologists working in the discovery, development and registration of agrochemicals, as well as scientists in related areas such as design and mode of action of pharmaceuticals. Developed in conjunction with Accelrys Ltd, Metabolic Pathways of Agrochemicals on CD-ROM is ideal for use alongside the two original print volumes. Fully cross referenced to both volumes and easy to use, the CD-ROM offers exact, substructure and similarity searching for parent, metabolite and entire transformation, and is indexed with original citations, test systems and a variety of keywords for generic searching. Windows compatible - Access 97 or 2000 required.
Keywords: Agricultural chemicals -- Metabolism.; elektronické knihy; electronic books